Bisleucocurine A, a novel bisindole alkaloid from Leuconotis griffithii - Nugroho, A.E.; Hirasawa, Y.; Hosoya, T.; Awang, K.; Hadi, A.H.A.; Morita, H. (Elsevier, 2010)
A novel bisindole alkaloid, bisleucocurine A (1), consisting of two strychnan skeletons with an N-1-C-17' and a C-12-C-2' bridges, was isolated from the leaves of Leuconotis griffithii and the structure was elucidated on the basis of spectroscopic data. Bisleucocurine A (1) showed cytotoxicity against various human cancer cell lines. (C) 2010 Elsevier Ltd. All rights reserved.